Transcriptional Profiles of Mating-Responsive Genes from Testes and Male Accessory Glands of the Mediterranean Fruit Fly, Ceratitis capitata - Scolari, Francesca (Public Library of Science, 2012)

(untitled)
BACKGROUND: Insect seminal fluid is a complex mixture of proteins, carbohydrates and lipids, produced in the male reproductive tract. This seminal fluid is transferred together with the spermatozoa during mating and induces post-mating changes in the female. Molecular characterization of seminal fluid proteins in the Mediterranean fruit fly, Ceratitis capitata, is limited, although studies suggest that some of these proteins are biologically active. METHODOLOGY/PRINCIPAL FINDINGS: We report on the functional annotation of 5914 high quality expressed sequence tags (ESTs) from the testes and male accessory glands, to identify transcripts encoding putative secreted peptides that might elicit post-mating responses in females. The ESTs were assembled into 3344 contigs, of which over 33% produced no hits against the nr database, and thus may represent novel or rapidly evolving sequences. Extraction of the coding sequences resulted in a total of 3371 putative peptides. The annotated dataset is available as a hyperlinked spreadsheet. Four hundred peptides were identified with putative secretory activity, including odorant binding proteins, protease inhibitor domain-containing peptides, antigen 5 proteins, mucins, and immunity-related sequences. Quantitative RT-PCR-based analyses of a subset of putative secretory protein-encoding transcripts from accessory glands indicated changes in their abundance after one or more copulations when compared to virgin males of the same age. These changes in abundance, particularly evident after the third mating, may be related to the requirement to replenish proteins to be transferred to the female. CONCLUSIONS/SIGNIFICANCE: We have developed the first large-scale dataset for novel studies on functions and processes associated with the reproductive biology of Ceratitis capitata. The identified genes may help study genome evolution, in light of the high adaptive potential of the medfly. In addition, studies of male recovery dynamics in terms of accessory gland gene expression profiles and correlated remating inhibition mechanisms may permit the improvement of pest management approaches.